2018
DOI: 10.2514/1.c034005
|View full text |Cite
|
Sign up to set email alerts
|

Aeroelastic Analysis of a Cycloidal Rotor Under Various Operating Conditions

Abstract: Access to the published version may require subscription. When citing this work, cite the original published paper. Louis Gagnon provides this scientific self-archived article free of charge. For more research info see LouisGagnon.com This article is the final submission, post-review, version of the following article:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Another important step was made by Wheatley [7,8], when he built an experimental stand on which he tested a 4-blade cycloidal rotor equipped with blades with the NACA 0012 profile. Author described the distribution and the way in which forces are generated on the rotor with determination of the relationships between them Important work was also performed in relation to the European CROP [9][10][11][12] (Cycloidal Rotor Optimized for Propulsion) project of 2015, which aimed to create a "radically different propulsion system for aerial vehicles". In a series of papers, the authors examined the influence of the geometrical properties of the cycloidal rotor itself on its aerodynamic efficiency and determined the optimal angles for MAVs equipped with a cycloidal rotor while hovering.…”
Section: Introductionmentioning
confidence: 99%
“…Another important step was made by Wheatley [7,8], when he built an experimental stand on which he tested a 4-blade cycloidal rotor equipped with blades with the NACA 0012 profile. Author described the distribution and the way in which forces are generated on the rotor with determination of the relationships between them Important work was also performed in relation to the European CROP [9][10][11][12] (Cycloidal Rotor Optimized for Propulsion) project of 2015, which aimed to create a "radically different propulsion system for aerial vehicles". In a series of papers, the authors examined the influence of the geometrical properties of the cycloidal rotor itself on its aerodynamic efficiency and determined the optimal angles for MAVs equipped with a cycloidal rotor while hovering.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of the cycloidal rotor is mostly met in propulsion systems of MAVs (micro air vehicles). In this field, a mention should be made of the European CROP (Cycloidal Rotor Optimized for Propulsion) project from 2015, which aimed to create a "radically different propulsion system for aerial vehicles" [1][2][3]. The authors demonstrated the possibility of creating a new propulsion system based on a cycloidal device called the PECyT (plasma enhanced cycloidal thruster) [4].…”
Section: Introductionmentioning
confidence: 99%